Antibacterial activity of Syzygium aromaticum seed: Studies on oxidative stress biomarkers and membrane permeability. (June 2016) - Ajiboye, T.O.; Mohammed, A.O.; Bello, S.A.; Yusuf, I.I.; Ibitoye, O.B.; Muritala, H.F.; Onajobi, I.B.
Abstract: Oxidative stress and membrane permeability as mode of antibacterial activity of aqueous extract of Syzygium aromaticum seeds against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus was investigated. The concentration of phytochemical constituents of Syzygium aromaticum was determined using gas chromatography. Syzygium aromaticum seeds contain eugenol acetate > β-carophyllene > eugenin > eugenol > methyl salicylate > β -humulene > rhamnatin > fernesol > α-copeane > β-ylangene > kaempferol > cinnamic acid > oleanolic acid > benzaldehyde > α-humulene > vanillin > α -cubebene > carvicol > benzoic acid. Syzygium aromaticum showed antimicrobial activity with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values as 0.06 and 0.10 mg/mL respectively. Time kill susceptibility by Syzygium aromaticum at MBC values showed significant decrease in the optical density and colony-forming unit (CFU) of Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus . Superoxide anion radical content of the bacterial cells increased significantly following exposure to the extract. In a similar vein, superoxide dismutase and catalase activities increased significantly, while the level of reduced glutathione reduced, malondialdehyde increased significantly in bacterial cells exposed to the extract. The extract at MBC also enhanced the leakage of 260 nm absorbing materials and outer membrane permeability. It is evident from the data generated from this study that aqueous extract of Syzygium aromaticum seeds enhanced membrane permeability and oxidative stress in Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus . Highlights: Syzygium aromaticum seed induced oxidative stress in E. coli, P. aeruginosa and S. aureus . Syzygium aromaticum seed enhanced membrane peroxidation in E. coli, P. aeruginosa and S. aureus . Syzygium aromaticum seed promote release of cytoplasmic constituents of E. coli, P. aeruginosa and S. aureus . Syzygium aromaticum seed depletes cellular glutathione level in E. coli, P. aeruginosa and S. aureus .